2006
DOI: 10.1245/aso.2006.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Local Failure Rate of Radiofrequency Ablation of Colorectal Liver Metastases

Abstract: Because accurate electrode placement is pivotal in achieving adequate tumor necrosis, RFA should not be performed percutaneously when electrode placement is impaired. We suggest that lesions >5 cm and lesions located near great vessels or adjacent organs should be treated with open RFA, thus allowing vascular inflow occlusion and complete mobilization of the liver. Lesions that are difficult to reach by electrodes should be approached by an open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 30 publications
5
78
2
1
Order By: Relevance
“…Distant recurrence (elsewhere in the liver or extrahepatic) rates vary from 28% to 84% [17,20]. Reported local recurrence rates (at the RFA site) range widely, from 2% to 60% [19,28,[31][32][33][34]. In our series 12% had local RFA site recurrence.…”
Section: Discussionmentioning
confidence: 65%
“…Distant recurrence (elsewhere in the liver or extrahepatic) rates vary from 28% to 84% [17,20]. Reported local recurrence rates (at the RFA site) range widely, from 2% to 60% [19,28,[31][32][33][34]. In our series 12% had local RFA site recurrence.…”
Section: Discussionmentioning
confidence: 65%
“…While some studies [11, 76 -79] have reported recurrence or persistence of metastatic disease at the site of the RFA to be Ͻ10%, other studies have reported local recurrence rates as high as 47% [80,81]. Survival following ablation is also difficult to interpret, because many patients who undergo this therapy are characterized by a number of poor prognostic factors (e.g., "unresectable" disease, multiple tumors, bilobar location, etc.…”
Section: Combined Local Therapy: Resection Plus Rfamentioning
confidence: 99%
“…Other factors, such as size of the tumour treatment margins and operator-dependent variables, can contribute to the efficacy of the technique 14,15 . One study compared 190 patients resected without rfa and 101 receiving rfa plus resection 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Survival at 4 years was 65% for hepatectomy that also included rfa compared with 36% for hepatectomy alone. Another study evaluated 87 patients managed with rfa only 15 . Local (hepatic) failure occurred in 47.2% of patients.…”
Section: Discussionmentioning
confidence: 99%